The Politics of the Visible in Asian North American Narratives - Ty, Eleanor Rose, 1958- (Book collections on Project MUSE., 2004)
Examining nine Asian Canadian and Asian American narratives, Eleanor Ty explores how authors empower themselves, represent differences, and re-script their identities as 'visible minorities' within the ideological, imaginative, and discursive space given to them by dominant culture. In various ways, Asian North Americans negotiate daily with 'birthmarks, ' their shared physical features marking them legally, socially, and culturally as visible outsiders, and paradoxically, as invisible to mainstream history and culture. Ty argues that writers such as Denise Chong, Shirley Geok-lin Lim, and Wayson Choy recast the marks of their bodies and challenge common perceptions of difference based on the sights, smells, dress, and other characteristics of their hyphenated lives. Others, like filmmaker Mina Shum and writers Bienvenido Santos and Hiromi Goto, challenge the means by which Asian North American subjects are represented and constructed in the media and in everyday language. Through close readings grounded in the socio-historical context of each work, Ty studies the techniques of various authors and filmmakers in their meeting of the gaze of dominant culture and their response to the assumptions and meanings commonly associated with Orientalized, visible bodies.